Empirical Study on Event Study Model on Biotech Stock Market - Umayi Ananda, Woro; Gursida, Hari; Indrayono, Yohanes (Journal of World Science, 2023)
Biotechnology today is used to develop and play an important role both in terms of the discovery of drug development that is a breath for the continuity of the pharmaceutical industry. The purpose of this research is to find out and analyze empirical studies on the event study model in the biotech stock market. This study uses a type of quantitative method, sampling using purposive sampling. Based on the results of the study, there is an influence of financial literacy, personal interest, and environment on interest in investing in the biotechnology stock market, there is an influence of financial literacy on interest in investing in the biotechnology capital market, there is an influence of personal interest on interest in investing in the biotechnology capital market, there is an influence of environment on interest in investing in the biotechnology capital market. Biotechnology plays an important role in the development of medicines and has a positive impact on the stock market and economy. Investing in biotech stocks requires adequate knowledge and a wise approach to avoid irrational investment practices and risks. It is expected that the younger generation will consider investing in the biotech sector, particularly in the pharmaceutical industry, to achieve sustainable profits.